Factors Affecting the Risk Non-Performing Sharia Commercial Bank Financing - Nurhadi Syaifudin Zuhri; Binti Nur Asiyah (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2023)
This study aims to examine and analyze the influence of internal and external factors on the risk of problem financing in Islamic commercial banks in Indonesia. This research uses a quantitative type. Data comes from the Financial Services Authority (OJK) and Bank Indonesia for the 2015-2022. The data were first tested using the classical assumption test, which included the normality test, multicollinearity test, and autocorrelation test and then analyzed using multiple linear regression analysis. The Robust Least Squares method is used in multiple linear regression analysis to overcome the problem of heteroscedasticity. The results show that the internal factors that are taken into account are the efficiency ratio (BOPO), capital adequacy ratio (CAR) and financing-to-savings ratio (FDR). At the same time, the external factor that is taken into account is the inflation rate. Based on the results of testing the hypothesis using the z test, it is concluded that only CAR and FDR significantly contribute to problem financing. In contrast, efficiency and inflation do not significantly affect problem financing in Islamic Commercial Banks in Indonesia. Â